(untitled) (London Journal of Engineering Research, 2022)
Dehydration of Natural Gas has been a subject of interest for decades due to the effect of wet gas on the system. Specifically, the gas’ heating value and its flow assurance are challenged coupled with not meeting markets’ specification. Besides these flow assurance and related issues, the hydrate in the gas quickly deactivate catalyst and burn less. This study attempts to economically dehydrate the gas using Triethylene Glycol (TEG) which has to be optimally regenerated and used for further dehydration process. The simulation and optimization of the dehydration process through absorption with TEG was carried out using Aspen HYSYS software and Design-Expert software respectively. The simulation was carried out using Glycol and Peng-Robinson as the thermodynamic fluid package. Effects of parameters such as TEG circulation rate, equilibrium stages of absorption column, operating conditions on the process efficiency were investigated. It was found that, lowering the pressure in the absorption column reduces the amount of hydrocarbons trapped in the wet TEG stream leaving the bottom of the absorber. The optimization of the Recycled TEG was carried out using the numerical optimization of the Design-Expert software, the experimental design was based on the Central Composite Design of the Response Surface Methodology of Design-Expert version 10, this optimization yield a relative increase in TEG recycled stream from 99.59 mole% to 99.89 mole% at an optimum operating parameters of 25oC, 6320 kpa and 1883 kgmole/h of the wet gas stream.